Risk Factors Associated With Carbapenemase-Producing Carbapenem-Resistant Enterobacteriaceae Positive Cultures in a Cohort of US Veterans. (11th May 2021) - Wilson, Geneva M; Suda, Katie J; Fitzpatrick, Margaret A; Bartle, Brian; Pfeiffer, Christopher D; Jones, Makoto; Rubin, Michael A; Perencevich, Eli; Evans, Martin; Evans, Charlesnika T; ,
Abstract: Background: Carbapenem-resistant Enterobacteriaceae (CRE) cause approximately 13 100 infections, with an 8% mortality rate in the United States annually. Carbapenemase-producing CRE (CP-CRE) a subset of CRE infections infections have much higher mortality rates (40%–50%). There has been little research on characteristics unique to CP-CRE. The goal of the current study was to assess differences between US veterans with non-CP-CRE and those with CP-CRE cultures. Methods: A retrospective cohort of veterans with CRE cultures from 2013–2018 and their demographic, medical, and facility level covariates were collected. Clustered multiple logistic regression models were used to assess independent factors associated with CP-CRE. Results: The study included 3096 unique patients with cultures positive for either non-CP-CRE or CP-CRE. Being African American (odds ratio, 1.44 [95% confidence interval, 1.15–1.80]), diagnosis in 2017 (3.11 [2.13–4.54]) or 2018 (3.93 [2.64–5.84]), congestive heart failure (1.35 [1.11–1.64]), and gastroesophageal reflux disease (1.39 [1.03–1.87]) were associated with CP-CRE cultures. There was no known antibiotic exposure in the previous year for 752 patients (24.3% of the included patients). Those with no known antibiotic exposure had increased frequency of prolonged proton pump inhibitor use (17.3%) compared to those with known antibiotic exposure (5.6%). Discussion: Among a cohort of patients with CRE, African Americans, patients with congestive heart failure, and those with gastroesophageal reflux disease had greater odds of having a CP-CRE culture. Roughly 1 in 4 patients with CP-CRE had no known antibiotic exposure in the year before their positive culture. Abstract : Being African American and having congestive heart failure or gastroesophageal reflux disease were associated with increased likelihood of a carbapenemase-producing carbapenem-resistant Enterobacteriaceae–positive culture. Of the cohort, 24.3% had no antibiotic exposure in the year before positive culture.